Relevance of User Education for Efficient Library Service:A Study in the Context of Five Laws - Jas, Nikhil Kumar (Journal of Information and Knowledge, 1999)
Defines user education and describes its objectives and components. Explains how users are being debarred from using library resources and facilities due to lack of proper user education programme. Justifies how user education is relevant for the fulfillment of the spirit of five laws of library science.